2017
DOI: 10.1038/s41598-017-01957-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Long Noncoding RNAs Deregulated in Papillary Thyroid Cancer and Correlated with BRAFV600E Mutation by Bioinformatics Integrative Analysis

Abstract: Papillary Thyroid Cancer (PTC) is an endocrine malignancy in which BRAFV600E oncogenic mutation induces the most aggressive phenotype. In this way, considering that lncRNAs are arising as key players in oncogenesis, it is of high interest the identification of BRAFV600E-associated long noncoding RNAs, which can provide possible candidates for secondary mechanisms of BRAF-induced malignancy in PTC. In this study, we identified differentially expressed lncRNAs correlated with BRAFV600E in PTC and, also, extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 60 publications
(86 reference statements)
1
20
0
Order By: Relevance
“…For the results of the pathway analysis in this study, we consulted the literature and retrieved more relevant information. ECM-receptor interactions have been found to play a role in the development of papillary thyroid carcinoma [38]. Activation of the p53 signaling pathway could induce In addition, we used the CMap database to find small molecules of drugs that might reverse the expression of thyroid cancer genes.…”
Section: Discussionmentioning
confidence: 99%
“…For the results of the pathway analysis in this study, we consulted the literature and retrieved more relevant information. ECM-receptor interactions have been found to play a role in the development of papillary thyroid carcinoma [38]. Activation of the p53 signaling pathway could induce In addition, we used the CMap database to find small molecules of drugs that might reverse the expression of thyroid cancer genes.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs can have regulatory functions to diversify the genetic output and, due to their high stability and association with the pathogenesis of human cancers, are promising diagnostic and prognostic biomarkers 19 - 21 . They may also function to amplify the malignancy and progression of cancer induced by other genomic alterations 70 . Although several lncRNAs are aberrantly expressed in PTC 23 - 27 , their key targets have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that, as members of noncoding RNAs (ncRNAs), microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) play essential roles in regulating the pathologic network of PTC in different stages . LncRNAs are defined as a cluster of transcripts with more than 200 nucleotides without protein‐coding potential, which were originally considered as transcriptional noise.…”
Section: Introductionmentioning
confidence: 99%